(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The integration of Artificial Intelligence (AI) and digital connectivity is driving a significant shift in education systems worldwide, offering unprecedented opportunities to improve efficiency, effectiveness, and decision-making processes, particularly in areas such as planning, administration, and student engagement. In Nigeria, the polytechnic education sector is at a critical juncture, with digital transformation presenting significant opportunities to enhance educational management practices. This study examines how AI tools and digital connectivity frameworks can improve administrative efficiency, data-driven decision-making, student support, and teaching methods within Nigerian polytechnics. Using a mixed-methods approach, the research combines surveys and interviews with around 200 participants from five polytechnics, including administrative staff, ICT officers, and academic leaders from selected polytechnic schools. Data analysis, using Likert-scale evaluations, shows increasing awareness and interest in AI solutions. However, challenges such as poor infrastructure, limited funding, and a lack of digital skills slow down widespread adoption. The study highlights the need for strategic policies, greater investment in ICT infrastructure, and targeted AI training programs. By sharing these findings, the research supports ongoing policy talks on digital transformation in higher education. It offers practical suggestions for developing smart, connected, and effective educational management systems in Nigeria’s polytechnic sector.